Dilated Cardiomyopathy: Phosphorus 31 MR Spectroscopy at 7 T - Stoll, Victoria M.; Clarke, William T.; Levelt, Eylem; Liu, Alexander; Myerson, Saul G.; Robson, Matthew D.; Neubauer, Stefan; Rodgers, Christopher T. (Radiology, 2016)
Purpose To test whether the increased signal-to-noise ratio of phosphorus 31 ( P) magnetic resonance (MR) spectroscopy at 7 T improves precision in cardiac metabolite quantification in patients with dilated cardiomyopathy (DCM) compared with that at 3 T. Materials and Methods Ethical approval was obtained, and participants provided written informe consent. In a prospective study, P MR spectroscopy was performed at 3 T and 7 T in 25 patients with DCM. Ten healthy matched control subjects underwent P MR spectroscopy at 7 T. Paired Student t tests were performed to compare results between the 3-T and 7-T studies. Results The phosphocreatine (PCr) signal-to-noise ratio increased 2.5 times at 7 T compared with that at 3 T. The PCr to adenosine triphosphate (ATP) concentration ratio (PCr/ATP) was similar at both field strengths (mean ± standard deviation, 1.48 ± 0.44 at 3 T vs 1.54 ± 0.39 at 7 T, P = .49), as expected. The Cramér-Rao lower bounds in PCr concentration (a measure of uncertainty in the measured ratio) were 45% lower at 7 T than at 3 T, reflecting the higher quality of 7-T P spectra. Patients with dilated cardioyopathy had a significantly lower PCr/ATP than did healthy control subjects at 7 T (1.54 ± 0.39 vs 1.95 ± 0.25, P = .005), which is consistent with previous findings. Conclusion 7-T cardiac P MR spectroscopy is feasible in patients with DCM and gives higher signal-to-noise ratios and more precise quantification of the PCr/ATP than that at 3 T. PCr/ATP was significantly lower in patients with DCM than in control subjects at 7 T, which is consistent with previous findings at lower field strengths.